2021
DOI: 10.1007/s00382-020-05600-z
|View full text |Cite
|
Sign up to set email alerts
|

A statistical–dynamical downscaling methodology for the urban heat island applied to the EURO-CORDEX ensemble

Abstract: Regional Climate Models (RCMs) are the primary climate information available to public stakeholders and city-planners to support local adaptation policies. However, with resolution in the order of ten kilometres, RCMs do not explicitly represent cities and their influence on local climate (e.g. Urban Heat Island; UHI). Downscaling methods are required to bridge the gap between RCMs and city scale. A statistical–dynamical downscaling methodology is developed to quantify the UHI of the city of Paris (France), ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 94 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…Wang et al (2015) revealed that the precipitation decreased when urban areas were artificially eliminated using the WRF with 3.3 km resolution. Also, the CORDEX suggested the impact of urbanization on climate as a theme on scientific challenges called flagship pilot studies (FPS) (Langendijk et al, 2019;Le Roy et al, 2021).…”
mentioning
confidence: 99%
“…Wang et al (2015) revealed that the precipitation decreased when urban areas were artificially eliminated using the WRF with 3.3 km resolution. Also, the CORDEX suggested the impact of urbanization on climate as a theme on scientific challenges called flagship pilot studies (FPS) (Langendijk et al, 2019;Le Roy et al, 2021).…”
mentioning
confidence: 99%
“…The larger ensemble spread for the lower quantiles of winter temperature (here Figure 4) can be due to the considerable sensitivity of winter temperatures on differences in the regional temperature field. Additionally, it may be due to the solid west-east air temperature gradient in winter in Europe and the snow-albedo feedback [31].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In the context of impact studies at local scale, requiring high-resolution climatic data, the use of km-scale convection permitting models (CPM) is increasing (Bamba et al, 2023;Le Roy et al, 2021;Tradowsky et al, 2023). Thanks to their high spatial resolution (less than 4 km), CPMs can represent convection explicitly without the need for parameterisation, thus reducing the associated model uncertainty (Fosser et al, 2024).…”
mentioning
confidence: 99%